HZ Ethiopia chickens: Scientists launch Ethiopian farm to breed healthy, bug resistant chickens - Associated Press (Associated Press, 2018)
1. Various shots of the chick hatching facility at the Addis Ababa International Livestock Research Institute (ILRI) 2. Mid of the research institute 3 . Wide of ILRI's new research and development facility with giant artwork of chickens 4. Close of chicks 5. Wide of chicken area 6. Various of chickens 7. SOUNDBITE: (English) Olivier Hanotte (Prof.), lead researcher "For agricultural species, like chicken cattle and so on, diversity is that the roots of productivity; improvement of productivity. If we want animals, chickens, who produce more eggs, who grow faster, which are more resistant we have to select them from a pool, from a pool of diversity. And this is why diversity entered the game. Without diversity there will be no breeding improvements." 8. Various shots of a worker working at ILRI research facility 9. SOUNDBITE: (English) Olivier Hanotte (Prof.), lead researcher "Today, Ethiopia is one of the richest country in terms of diversity. So we have a huge access to material that we can compare and work with. So having this facility in Ethiopia, which incidentally is also the cradle of humanity as we know, is actually very important and will allow us to do more (than) if we had to do it somewhere else." 10. Various shots of the ILRI chickens 11. SOUNDBITE: (English) Tadelle Dessie, Senior animal geneticist, ILRI research facility "Whatever we will be doing this facility in relation to improvement, productivity and production improvement, will trickle down to benefit the poor smallholder farmers in Ethiopia and elsewhere." 12. Pull focus through hand held microscope of the 'book of genome' 13. SOUNDBITE: (English) Tadelle Dessie, Senior animal geneticist, ILRI research facility "The local contributes to the global. And the global contributes to the local. The global cannot exist without the local. And the local cannot exist without the global. So we are trying to bring that one and use art to send a message to the community, to send a message to the development practitioners, to send a message to the farmers." 14. Various shots of the chick hatching facility 15. SOUNDBITE: (English) Koen Vanmechelen, visual artist "This chicken, which is actually a global animal you can find it everywhere, but at the same time it is also very local because everybody adapted to their area. And that is fascinating because that is culture." 16. Wide of Karakore neighborhood, a suburb of Addis Ababa 17. Mid of a rundown bridge, 18. Mid of a farmer's house, 19. Wide of traditional chicken pen 20. Mid of Fitsum Gebrehana, chicken farmer, entering his chicken pens 21. Close of the farmer cleaning his foot with disinfectant 22. Mid of Gebrehana's wife entering the chicken pen 23. Various shots of chickens owned by Gebrehana and his wife, 24. SOUNDBITE: (Amharic) Fitsum Gebrehana, Farmer "In earlier times, our chickens used to frequently be attacked by disease. And we were not providing the right care for our chickens. We used to just let them wander around all day. And now my wife and I are doing all the necessary care and attention and we do that in turns. And that way we were able to do other things as well." 25. Various shots of the farmer's chicken farm 26. SOUNDBITE:(Amharic) Fitsum Gebrehana, Farmer "We sell a portion of the eggs that are produced from this small farm and we consume some of them as well. The income from this covers some house expenses. Also after selling some cocks some time ago, I have managed to buy few sheep and that is helping my family economically. And because of that change in our livelihood, I want to expand my chicken business even more." 27. Close of a chicken laying eggs 28. Close of the eggs